Wasserpreise zwischen Kartellkontrolle und Nachhaltigkeit - Erik Gawel; Norman Bedtke (Wirtschaftsdienst, 2013)
Die Wasserpreise in Deutschland werden im Zuge der neuerdings aktivierten kartellrechtlichen Missbrauchsaufsicht verstärkt kontrovers diskutiert. Insgesamt ist der Regulierungsrahmen der Wasserwirtschaft unter Veränderungsdruck. Dabei steht die Entgeltkontrolle im Mittelpunkt des Interesses. Eine allein auf Effi zienz setzende Preiskontrolle wird aber der komplexen Zielstellung von Wasserpreisen nicht gerecht. Zwar ist der Wassersektor kein effizienzfreier Ausnahmebereich, doch die konkurrierenden Vorgaben des Gebühren-, Wettbewerbs- und Wasserrechts müssen aufeinander abgestimmt und Nachhaltigkeitsprobleme einer Effizienzregulierung stärker beachtet werden. – – The regulatory framework of the German water sector is currently undergoing a reorientation process at both the EU and national levels. Price regulation of water utilities is particularly controversial. Recently, some national antitrust authorities have significantly increased their oversight of abusive practices. However, the focus of the regulation in this field is exclusively on efficiency while neglecting other pricing objectives (e.g. internalisation of environmental costs). The article examines the current practice of different price regulation schemes (cost plus pricing and control of abusive practice) and identifies its shortcomings. It is shown that different regulating principles of relevant laws (law of charges, competition law and water law) have to be better aligned and sustainability issues need to be taken into account in theory and practice when addressing efficiency requirements for water utilities.
Keywords: D42; L40; Q01; 330; Wasserpreis; Kartellrecht; Wirtschaftliche Effizienz; Nachhaltigkeit; Deutschland